“ELEKTRON (VIRTUАL) KUTUBXONАLАRNI YARАTISH MАSАLАLАRI” - Qo‘ldosheva , Komila Boboxolovna (INTERNATIONAL CONFERENCES, 2023)
By electronic we mean a library with a wide range of documents in electronic form that can be accessed through data networks. With the establishment of e-libraries, there is a need to prepare librarians and users to work in e-libraries, training using e-libraries, including distance learning